1996
DOI: 10.1177/027347539601800203
|View full text |Cite
|
Sign up to set email alerts
|

Using Peer Evaluations to Assess Individual Performances in Group Class Projects

Abstract: The use of various kinds of group projects is common in many types of marketing courses. A major problem in such courses is the equitable grading of group members based on the accountability of individual performances. This article provides an approach to using peer evaluations to assess individual performances within a group so that grades may be assigned in an equitable manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 5 publications
0
28
0
Order By: Relevance
“…Similarly, to assess their perceptions of grade fairness, respondents were asked whether their grade reflected their contribution to the project (1 = grade lower than my contribution, 7 = grade accurately reflected my contribution). The scale items were developed by the authors drawing from similar items reported in the literature (Beatty et al, 1996;Deeter-Schmelz et al, 2002;Johnston & Miles, 2004;McCorkle et al, 1999;Pfaff & Huddleston, 2003;Strong & Anderson, 1990).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, to assess their perceptions of grade fairness, respondents were asked whether their grade reflected their contribution to the project (1 = grade lower than my contribution, 7 = grade accurately reflected my contribution). The scale items were developed by the authors drawing from similar items reported in the literature (Beatty et al, 1996;Deeter-Schmelz et al, 2002;Johnston & Miles, 2004;McCorkle et al, 1999;Pfaff & Huddleston, 2003;Strong & Anderson, 1990).…”
Section: Methodsmentioning
confidence: 99%
“…If the grade is low, they will blame it on the social loafer and will engage in counterfactual thinking about how their grade could have been higher had they teamed up with better contributing students. Even when the project grade is high, some students would be unhappy sharing it with those whom they consider to be social loafers (Beatty et al, 1996). From their perspective, though they deserve the high grade because of all the extra work they put in to compensate for the lack of performance on the part of social loafers, they may find it unacceptable to share the same grade with those who did not contribute.…”
Section: Consequences Of Social Loafingmentioning
confidence: 99%
“…If the peer evaluation is administered confidentially and does not include self‐evaluations, the inflationary effect is mitigated and tends to be an accurate assessment (Lejk & Wyvill, 2001). Research on peer evaluation has examined the reliability and validity of peer ratings (Beatty, Hass, & Seiglimpaglia, 1996; Morahan‐Martin, 1996), the bias of peer ratings (Ghorpade & Lackritz, 2001), and the development of an evaluation instrument (Johnson & Smith, 1997; Levi & Cadiz, 1998). Very little research has examined what team member characteristics and what team activities affect peer evaluations.…”
Section: Peer Evaluationmentioning
confidence: 99%
“…Group projects provide opportunities for students to learn from each other (Beatty et al, 1996). In a group setting, students not only acquire the knowledge that other group members offer but also acquire skills in group dynamics and leadership that should prove valuable in their future business careers.…”
Section: Theoretical Background and Supporting Literaturementioning
confidence: 99%
“…This research indicates that peer assessment reflects the perspective of peer students who are in close contact and are familiar with group member behaviors and characteristics that may not otherwise be apparent to an instructor (Barrett, 1996;Cederblom & Lounsbury, 1980). Research on peer evaluations often examines issues such as the development and validity of an evaluation instrument (Johnson & Smith, 1997;Levi & Cadiz, 1998;Smith, 1998), the validity (Beatty et al, 1996) and reliabil-ity (Morahan-Martin, 1996) of peer ratings in measuring student performance, and the potential bias of peer ratings (Ghorpade & Lackritz, 2001;Hass, Hass, & Wotruba, 1998). Very few studies, however, have examined students' perceptions of peer evaluations and their motivation to participate in the evaluation.…”
mentioning
confidence: 99%